The Effect of Physical Fitness on Body Fat - Asep Prabowo; Sofyan Hanif; James Tangkudung (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2021)
This study aimed to determine the effects of physical fitness on body fat. This research was conducted in National Sports Committee of Indonesia, specifically in Karawang Regency, and selected the athletes as the respondents. The researcher implemented causal studies and path analysis testing. Fourteen (14) respondents were selected by purposive sampling. The data were collected by using Harvard step test in order to measure the physical fitness, and Bioelectrical Impedance Analysis (BIA) data in order to measure the body fat. This study found that the path coefficient value of thephysical fitness on body fat is -0.212, while the value of t-count is -2.468. Therefore, the value of t-count is smaller than t-table, while the degree of freedom = 9 and α = 0.05 ,such as -2.26, and the probability value of Sig. (0.036) <significant level (0.05). Hence, H0 is rejected and H1 is accepted. In other words, physical fitness significantly has direct negative effect on body fat. In conclusion, physical fitness has a significant and direct negative effecton body fat, even when the athlete’s physical fitness is better, it does not guarantee his body fat is also good